Correlated divergence of female and male genitalia in replicated lineages with ongoing ecological speciation. (7th May 2019) - Greenway, Ryan; McNemee, Rachel; Okamoto, Alexander; Plath, Martin; Arias‐Rodriguez, Lenin; Tobler, Michael
Abstract: Divergence of genital traits among lineages has the potential to serve as a reproductive isolating barrier when copulation, insemination, and fertilization are inhibited by incompatibilities between female and male genitalia. Despite widespread evidence for genital trait diversity among closely related lineages and coevolution of female and male genitalia within lineages, few studies have investigated genital evolution during the early stages of speciation. We quantified genital variation in replicated population pairs of Poecilia mexicana with ongoing ecological speciation between sulfidic (H2 S containing) and nearby nonsulfidic habitats. These analyses revealed rapid and correlated divergence of female and male genitalia across evolutionarily independent population pairs exposed to divergent selection regimes. Both sexes exhibited convergent evolution of genital traits among populations inhabiting similar habitat types. Our results demonstrate that genital evolution can occur during the early stages of speciation‐with‐gene‐flow, potentially as a result of variation in the intensity of sexual conflict among populations. Our results suggest genitalia may contribute to early stages of divergence and challenge the generality of previously suggested mechanisms of genital evolution in poeciliids.